Penetrasi Konsep Hibah Dalam Proses Pembagian Waris - Nuryamin, Nuryamin; Farid, Diana (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
Basically, a property owner has the right and freedom to give (gift) his property to anyone, including his children, provided that the gift (gift) does not cover and does not reduce other rights as heirs. If the terms and conditions are met, then the grant is valid. Meanwhile, the right of the recipient of the gift to the inheritance is absolutely his share as an heir without having to be reduced as a result of obtaining the gift as long as the heir does not lose his inheritance rights, because the gift has nothing to do with inheritance. Thus, the inherited assets obtained are not counted as inheritance, so that he is entitled to inheritance assets according to what he should receive as part of the inheritance after the parent (heir) dies. Gift giving in Islamic Law is limited to a maximum of 1/3 (one third) of the grantor's assets. In the event that gifts are made to children (heirs), the limitation is that gifts must be made based on the principle of justice. This limitation on grant giving is provided to protect the rights of the heirs after the grantor dies, so the main aim of the grant is to strengthen friendly relations. Apart from the maximum limits regulated in Islamic Law (KHI), Customary Law and BW also provide the same limits in granting grants. This is intended to protect the rights of the heirs and to avoid losses suffered by the heirs whose share cannot be reduced according to law, so that with this gift the share of the heirs becomes less than what they should receive.